APAKAH BREAKPOINT CHLORINATION SELALU APLIKATIF UNTUK MENGOLAH LIMBAH CAIR RUMAH SAKIT? - Maya Shovitri (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2011)
Chlorination is one of the wastewater treatment techniques are often used to kill pathogenic coliform bacteria in hospital wastewater treatment. However, the application of chlorine was positively correlated with the formation of toxic organohalogen compounds. Therefore, chlorine application should be based on the calculation of breakpoint chlorination (BPC) for environmental protection. By using wastewater samples from a hospital that use 5 mg/L chlorination dose, this study was conducted for determining the chlorination applicability at BPC. BPC point was determined by iodometric titration method and potassium permanganate. Based on the titration of potassium permanganate, wastewater samples containing organic materials of 39.79 mg/L, the active chlorine doses were tested at 30, 35, 40, 45, 50, 55, 60, and 65 mg/L. At all incubation periods of 0, 15, 30 and 45 minutes the BPC occurs at similar concentration of 55 mg/L. The dose was able to reduce coliform bacteria concentrations from 106 cells/100 mL to 200 cells/100 mL. If chlorination was only considered as a desinfectant, chlorination at BPC was questionable, because at 10 mg/L the coliform bacteria concentration could be reduced to 200 ml. In addition, the application of 55 mg/L chlorination left residual chlorine of 43 mg/L in average into the environment. This residual chlorine concentration was relatively high when compared to the real application (residual chlorine of 5 mg/L), although in this chlorine concentration the residual chlorine left coliforms of 105 ml cells/100 mL.